SPIRITUALITAS IBADAH YAHUDI DALAM EKARISTI DAN DAMPAKNYA BAGI KETERLIBATAN UMAT KATOLIK INDONESIA DALAM KEHIDUPAN SOSIAL-POLITIK - Vinsensius Rixnaldi Masut (Al Hikmah, 2022)
This study aims to describe the spirituality of the Jewish liturgy found in the celebration of the Eucharist and its impact on the involvement of Indonesian Catholics in socio-political life. This study emerged from the concern that the Indonesian people, who are actually rich in spiritual values, in fact behave badly in their socio-political life which is characterized by acts of corruption. This research raises the awareness of Catholics to be actively involved in socio-political life and color it with gospel values. This vocation will be realized if the Eucharist as the source and summit of Christian life really renews and encourages Catholics in Indonesia to take part in God's mission to save all people. So the Eucharist must draw from the spirituality contained in Jewish worship as the locus of a personal encounter with the God who saves. This study uses the qualitative method by conducting a literature study on the liturgy in the Jewish and Christian traditions and then connecting them to today's socio-political issues. This study has found that the spirituality of the Jewish liturgy as the root of the Christian liturgy is able to bring renewal in the lives of Catholics, especially their involvement in realizing justice, peace, and social welfare.